AVALIAÇÃO INSTITUCIONAL NA EDUCAÇÃO BÁSICA: UMA ANÁLISE DA PRÁTICA DA EDUCAÇÃO ADVENTISTA - FERREIRA, PATRICK VIEIRA (2016)
The theme of this thesis is institutional assessment in elementary education. For that purpose, it offers an analysis of the evaluation process with emphasis on the assessment tool used by Adventist elementary schools in São Paulo, considering that Adventist education has become a consistent part within the structure of the Seventh-day Adventist Church. The main goal for this study was to understand how the Adventist Educational Network undertakes its institutional assessment. The research method included a literature review of the main theoreticians of public policies, private education, and institutional evaluation. It also included a documentary examination of the assessment tool used in the institutional evaluation process. The study also focuses the historical context of the development of private schools in Brazil, highlighting relevant aspects of their relationship with the State. It also briefly presents the history of the Seventh-day Adventist Church in the United States (US) and in Brazil, in order to contextualize the emergence of the Adventist educational system, as well as its educational philosophy, seeking to understand the origins of this religious group that operates for more than a century in the Brazilian educational scenario. The study then discusses important aspects of institutional evaluations. Finally, it presents a summary of the evaluation process and an analytical description of the institutional assessment tool for SDA elementary schools. In the end, no indications that the Adventist concept of educational evaluation is different from traditional approaches were found. However, the Adventist concept of institutional assessment shows more strongly a concern for maintaining a continuous and systematic evaluation process.